A influência da arte-educação, nas histórias de vida, dos alunos de escolas públicas, do ensino fundamental II e médio, na região metropolitana de Salvador - Sganzerlla, Evelin Sibele Ramalho (2012)
This dissertation consists of an analysis of the influence of non-regular school curriculum projects of art education (Rádio Juba and Hip-Hop) over life stories, and hence the civic education of adolescents from public schools in the Metropolitan Region of Salvador. The first chapter gives a historical overview of art in the world. Moreover, it exposed a panorama of art education in Brazil from its early years to the present day. The second chapter discusses the concept of art education and how it has been used today. This concept is an instrument that carries individuals, more specifically teenagers, from the dream dimension to reality and preparing them to use critical-creative reflection of the ethical and cultural values devised by mankind. The third chapter tells life stories that will be shown later, these stories take place on the island of Itaparica, located in the Metropolitan Region of Salvador. The fourth and last chapter shows from students and teachers answers - the influence of the projects of art education along with their humanization path. The answers are analized considering the individuality of each of the teenagers and teachers interviewed, as well as the historical context of these projects. The answers are also analized considering how they were and have being performed in the case of hip-hop. The dissertation suggests, in a broader aspect, a biographical study of the researcher - she was and still is part of these people lives and vice versa. Finally, it was concluded that people's lives are connected like a huge web. And, so, whatever changes in attitude, there will be a positive interference in society as a whole, since it focused on the ideals of human rights, ethics and consciousness. These objectives, both in conceptual, attitudinal or procedural are urgently needed to ensure the survival of mankind on our planet.